Microwave dielectric loss of thermally stressed MgTiO3 via TEM observation - Yoo, Sun-Hi; Yoon, Ki Hyun; Choi, Ji-Won (SPRINGER, 2008)
The influence of cooling rate on the dielectric loss of MgTiO3 ceramics at microwave frequencies via thermal stress and TEM was investigated. The specimens were cooled down with 1, 5, 30 degrees C/min and air-quenching from the sintering temperature of 1,350 degrees C. As the cooling rate increased, Q.f value decreased due to an increase of the crystallographic strain. The line defects such as dislocations increased with an increase of cooling rate except the specimen cooled down at 1 degrees C/min, which showed no dislocation. This result revealed that the line defects contribute to the deterioration of dielectric losses.
Keywords: THIN-FILMS; CERAMICS; FREQUENCIES; QUALITY; STRAIN